MULTIMODAL IMAGING IN TYPE 2 IDIOPATHIC MACULAR TELANGIECTASIA. Issue 4 (April 2015) - Sallo, Ferenc B.; Leung, Irene; Clemons, Traci E.; Peto, Tunde; Bird, Alan C.; Pauleikhoff, Daniel
Abstract : Background: Macular telangiectasia Type 2 is a bilateral, progressive potentially blinding retinal disease characterized by both vascular and neurodegenerative signs that have been documented using different imaging techniques. The correlation between macular telangiectasia Type 2 signs from various imaging modalities is unknown. Our aim was to investigate the relationship of various macular telangiectasia Type 2 signs using fundus fluorescein angiography, optical coherence tomography and dual-wavelength autofluorescence images. Methods: Participants were selected from the macular telangiectasia Type 2 Natural History Observation Study, based on a confirmed diagnosis and the availability of images. Signs in fundus fluorescein angiography, dual-wavelength autofluorescence, and optical coherence tomography images were graded according to standardized categories, and agreement among the multimodel imaging was assessed statistically. Results: One hundred and ninety-one eyes of 96 patients were examined. Significant correlations were found between early and late fundus fluorescein angiography (ρ = 0.82, P < 0.0001), luteal pigment loss and early/late fundus fluorescein angiography signs (ρ = 0.52, P < 0.0001 and ρ = 0.62, P < 0.0001, respectively), inner and outer segment break length and pigment loss (Class 1 vs. 2/3, P < 0.0001; Class 2 vs. 3, P = 0.04). Correlation between pigment loss and retinal spaces/atrophic retinal restructuring was fair (κ = 0.25–0.33). Bilateral symmetry was slight to substantial (κ = 0.18–0.62). Conclusion: Our data demonstrate the relative extent of neurodegenerative and vascular signs; it may be useful for designing systems for staging disease severity using multimodal imaging and may also provide clues to the pathogenesis of the disease. Abstract : The relative extent and progression patterns of neurodegenerative and vascular signs in macular telangiectasia Type 2 in fluorescein angiography, optical coherence tomography, and dual-wavelength autofluorescence images show significant correlations, which imply a common cause.